2022
DOI: 10.1021/acs.jpca.2c03305
|View full text |Cite
|
Sign up to set email alerts
|

Prenol as a Next-Generation Biofuel or Additive: A Comprehension of the Hydrogen Abstraction Reactions by a H Atom

Abstract: Thermal rate coefficients for the hydrogen abstraction reactions of prenol (3-methyl-2-butenol) by a hydrogen atom were calculated with the multipath canonical variational theory with small-curvature tunneling (MP-CVT/SCT). The conformational search was performed with a dual-level approach, and the multistructural torsional anharmonicity effects were corrected through the rovibrational partition function calculated with the multistructural method based on a coupled torsional potential (MS-T­(C)). This methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Figure S1 of the Supporting Information depicts the dihedral angles used in this search. In concordance with our previous study, [9] seven conformers (including the enantiomers) were found in the for the prenol, with the A + G − as the most stable structure. For the HA from the OH group of prenol (TS abs‐OH ), 14 conformations within 1.35 kcal/mol were located.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Figure S1 of the Supporting Information depicts the dihedral angles used in this search. In concordance with our previous study, [9] seven conformers (including the enantiomers) were found in the for the prenol, with the A + G − as the most stable structure. For the HA from the OH group of prenol (TS abs‐OH ), 14 conformations within 1.35 kcal/mol were located.…”
Section: Resultssupporting
confidence: 92%
“…Although the previous study has been dedicated to the production [3–6] and the oxidation, [7–9] its detailed combustion mechanism, the preferred radical or adduct formation, and temperature and pressure dependence still need to be fully understood. Combining experimental and theoretical results, Mohamed et al [10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the MS-CVT/SCT method, the MP-CVT/SCT method gives a more realistic description of the process of chemical reactions and gives a more accurate rate constant, as examined in the literature studies. 227–231…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…where F SS-T TS,p is the single-structural torsional anharmonicity factor of the TS for reaction path p and P k SCT p G CVT p F SS-T TS;p can be integrated into a reaction correction factor considering the tunneling, recrossing, and torsional anharmonicity of reaction path p. Compared with the MS-CVT/SCT method, the MP-CVT/ SCT method gives a more realistic description of the process of chemical reactions and gives a more accurate rate constant, as examined in the literature studies. [227][228][229][230][231] During the MS-T factor calculations, all the torsions in the molecule should be simultaneously rotated by 01, 1201, and À1201, to generate the initial possible conformers, which are further optimized using a selected density-functional-theory (DFT) method. For a large flexible molecule with the number of torsions 46, however, it is quite unaffordable and challenging to optimize such numerous initial conformers.…”
Section: Multi-path Canonical Variational Theorymentioning
confidence: 99%